Recent developments of composite separators based on high-performance fibers for lithium batteries. (November 2022) - Yu, Luyang; Gu, Jiayi; Pan, Chen; Zhang, Jingyi; Wei, Zhenzhen; Zhao, Yan
Graphical abstract: Abstract: The separator, being an essential component of lithium batteries, has a significant impact on the battery's safety and performance. In recent years, high-performance fibers, which refer to a new generation of synthetic fibers with high strength, high modulus, high temperature resistance, corrosion resistance, flame retardancy, and low density, have been extensively applied as raw or substrate materials in the field of separator for lithium batteries. Therefore, in this review, we begin our analysis by pointing out the shortcomings and issues with currently available commercial polyolefin separators, followed by a summary of the remedies to these issues. Then, we summarize some recently reported high-performance fiber-based separators and a comprehensive analysis is given by highlighting the technologies employed to enhance the safety and/or performance for lithium-ion or lithium-sulfur batteries. Finally, we provide an overview of the future development direction of high-performance fiber-based separators and suggest a few concerns that could be investigated further in this field of research. We hope such a review could shed lights for separator researches dedicated on improving battery safety and performance in the future.